Digital Entrepreneurship with Training in Making Handicraft Accessories for Students at the PGAI Padang Orphanage - MUHAMMAD, ABULWAFA; Mutiana Pratiwi; Rima Liana Gema (KPN Kopertis X, 2025)
The PGAI Foundation (Persatuan Guru Agama Islam) is a foundation that manages orphanages, schools and several other units in the city of Padang. Specifically, the children living in the orphanages come from various backgrounds and school age levels. They live and attend school at schools managed by the foundation, and some also attend public schools. One of the problems faced by these children is that they are accustomed to waiting for donations from donors for various activities. Although this is not the case for every child, it is certainly not good for their future. We provide handicraft training in the form of making accessories using digital technology. The students are given several product design examples and then given the freedom to develop their own products. The products produced are accessories such as bracelets, necklaces, rings and others made from beads. After the students are able to make the products, they are given knowledge on how to package the products. The students are also equipped with knowledge on how to utilise digital technology in obtaining product design references, promotion and marketing of their products. After this training, the children in the orphanage have acquired the skills to make various accessory products and have knowledge of digital entrepreneurship. This training has produced over 50 pieces of accessory products, including bracelets, rings, and several other items that are ready for marketing.